Cities' role in environmental sustainability policy: The Italian experience. (April 2021) - De Matteis, Fabio; Preite, Daniela; Striani, Fabrizio; Borgonovi, Elio
Abstract: The environmental dimension of sustainability implies the role of cities, considering their institutional vocation to territorial management and their proximity to the needs expressed by the community. This paper aims to investigate the implementation of a sustainable approach by cities in the realization of environmental policies. The methodology followed is regression (GLS method) that relates the expenses for the environmental policy of a sample of Italian cities (116) to some environmental indicators for the same municipalities (considering 2003–2011). Furthermore, t -test methodology is applied to compare the sample average values to the Italian average values of the selected environmental indicators. The paper takes into account not only a specific phase of sustainability, but it also considers the whole sustainability approach. In fact, the research connects the financial starting point of environmental policy (city's environmental financial commitment) to its environmental impacts (environmental indicators). The results obtained show that the investigated cities, on the one hand, direct environmental expenses to critical factors affecting environmental sustainability but, on the other hand, their environmental policies are not very effective. The research output gives useful information to city managers and politicians in order to focus their environmental policy on a sustainability approach that is effectiveness oriented. Highlights: The environmental dimension of sustainability implies the role of cities. This paper aims to investigate the cities' sustainable approach in the realization of environmental policies. Sustainability approach is the relation between financial input, output andimpact on environmental problems (outcome). The methodologies followed are regression (GLS method) and t-test, on a sample of Italian cities (116) for 9 years. The results show thatcitiesdirect expenses to sustainability issues buttheir environmental policies are ineffective.